(1 point) A hollow steel ball weighing 4 pounds is suspended from a spring. This stretches the spring 12 feet. The ball is started in motion

Question

(1 point) A hollow steel ball weighing 4 pounds is suspended from a spring. This stretches the spring 12 feet. The ball is started in motion from the equilibrium position with a downward velocity of 2 feet per second. The air resistance (in pounds) of the moving ball numerically equals 4 times its velocity (in feet per second) . Suppose that after t seconds the ball is y feet below its rest position. Find y in terms of t. (Note that the positive direction is down.) Take as the gravitational acceleration 32 feet per second per second.

in progress 0
Evelyn 2 weeks 2021-10-01T18:01:32+00:00 1 Answer 0

Answers ( )

    0
    2021-10-01T18:03:05+00:00

    Answer:

    (-0.377 – 1.117i)texp(-0.5 + 1.55i)t

    Step-by-step explanation:

    When the steel ball of mass m = 4 pounds is first suspended, the spring extends a distance of y₀ = 12 ft. From ky₀ = mg , k = mg/x₀ where k is the spring constant, and g = 32 ft/s² So, k = mg/y₀ = 4 × 32/12 = 10.67  

    The force of air resistance F = -4v

    The spring force after it has been extended y ft is F = -ky

    The net force on the steel ball is thus F = ma = -4v – ky

    -4v – ky = ma (v = dy/dt = y’ and a =dy/dt = y”)

    -4v – ky – ma = 0 ⇒ 4v + ky + ma = 0 (v = dy/dt = y’ and a =dy/dt = y”)

    4y’ + ky + my” = 0 ⇒ my” + 4y’ + ky = 0

    y” + 4y’/m + ky/m = 0

    y” + 4y’/4 + 32y/12 = 0

    y” + y’ + 8y/3 = 0

    3y” + 3y’ + 8y = 0. Let y” = D², y’ = D, y = 1

    3D² + 3D + 8 = 0

    Using the quadratic formula,

    D = [-3 ±√(3² – 4 × 3 × 8)]/(2 × 3) = [-3 ±√(9 – 96)]/(6) = [-3 ±√( – 87)]/(6) = [-3 ±√( – 9.33)]/(6) = -0.5 ±√-1.55 = -0.5 ± 1.55i

    y(t) = C₁exp(-0.5 + 1.55i)t + C₂texp(-0.5 + 1.55i)t

    y'(t) = (-0.5 + 1.55i)C₁exp(-0.5 + 1.55i)t + (-0.5 + 1.55i)C₂texp(-0.5 + 1.55i)t + (-0.5 + 1.55i)C₂exp(-0.5 + 1.55i)t

    y(0) = 0, y'(0) = 2

    y(0) = C₁exp(-0.5 + 1.55i) × 0 + C₂× 0 ×exp(-0.5 + 1.55i) × 0

    y(0) = C₁ exp(0)  + 0 = C₁

    0 = C₁

    C₁ = 0

    y'(0) = (-0.5 + 1.55i)C₁exp(-0.5 + 1.55i) × 0 + (-0.5 + 1.55i)C₂ × 0 × exp(-0.5 + 1.55i) × 0 + (-0.5 + 1.55i)C₂exp(-0.5 + 1.55i) × 0

    2 =  (-0.5 + 1.55i) × 0 × exp(0) + 0 + (-0.5 + 1.55i)C₂exp(0)

    2 =  0 + 0 + (-0.5 + 1.55i)C₂

    2 = (-0.5 + 1.55i)C₂

    C₂ = 2/(-0.5 + 1.55i) = 2(-0.5 – 1.55i)/2.6525 = (-1 – 3.1i)/2.6525 = -0.377 – 1.117i

    So,

    y(t) = C₁exp(-0.5 + 1.55i)t + C₂texp(-0.5 + 1.55i)t

    = 0 × exp(-0.5 + 1.55i)t + (-0.377 – 1.117i)texp(-0.5 + 1.55i)t

    = 0 + (-0.377 – 1.117i)texp(-0.5 + 1.55i)t

    = (-0.377 – 1.117i)texp(-0.5 + 1.55i)t

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )